Wealthy choices : - Tzougros, Penelope S. (J. Wiley, 2004)
No matter what your current financial situation, there are small and easy steps you can take to improve it. Financial planning expert Penelope Tzougros outlines these steps in this comprehensive and insightful book. You'll be introduced to seven competencies that will help you achieve a balanced financial life–so you’ll be at ease with your money. The competencies discussed include: valuing, paying the bills, losing, leveraging, dreaming, growing, gifting.